2000
DOI: 10.1002/etc.5620190314
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of waterborne strontium uptake in the common carp, Cyprinus carpio, at different calcium levels

Abstract: Abstract-The uptake kinetics of strontium in the common carp (Cyprinus carpio) were characterized in vivo, exposing preacclimated fish to a wide range of Sr 2ϩ (0.27 M-10.0 mM) and Ca 2ϩ (10 M-10 mM) concentrations in water; 85 Sr, 45 Ca, and 47 Ca were used as tracers in determining the uptake, and the possibility of adsorption of the tracers to the exterior of the fish were verified. The uptake rates were determined in the whole body, gills, and blood of the fish after an exposure period of 3 h and were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
3
13
1
Order By: Relevance
“…For example, in the gills of chub from the Sutla River, Sr and Ca were positively associated (R 2 = 0.356, p < 0.0001). This finding was opposite to previous reports that Sr and Ca inhibit each other's uptake completely competitively on the level of the whole organism, as well as in the gills of common carp (Cyprinus carpio) (Chowdhury et al 2000; Chowdhury and Blust 2001), due to uptake of both elements through Ca transport systems located in the chloride cells of gills (Flik et al 1995). In the natural aquatic systems, metals are present in different chemical forms, and, often, metal complexation with water-soluble ligands decreases metal uptake by aquatic organisms.…”
Section: Association With the Level Of Exposurecontrasting
confidence: 99%
“…For example, in the gills of chub from the Sutla River, Sr and Ca were positively associated (R 2 = 0.356, p < 0.0001). This finding was opposite to previous reports that Sr and Ca inhibit each other's uptake completely competitively on the level of the whole organism, as well as in the gills of common carp (Cyprinus carpio) (Chowdhury et al 2000; Chowdhury and Blust 2001), due to uptake of both elements through Ca transport systems located in the chloride cells of gills (Flik et al 1995). In the natural aquatic systems, metals are present in different chemical forms, and, often, metal complexation with water-soluble ligands decreases metal uptake by aquatic organisms.…”
Section: Association With the Level Of Exposurecontrasting
confidence: 99%
“…Such linear uptake has already been observed for vertebrates (Chowdhury et al 2000), although for a shorter exposure time (7 h). This result is therefore one of the first showing linear uptake over several days for calcifying organisms such as corals.…”
Section: Discussionsupporting
confidence: 69%
“…The CF values integrated in our study across eight sites and four earthworm species encompassed the range reported by Krivolutsky et al [24] but spanned from 0.10 to 1.42, with the highest values being recorded in soils with low strontium concentrations, and vice versa. This suggests the possibility that for soils with high strontium levels, earthworm uptake of the cation approaches saturation in a fashion analogous to that convincingly demonstrated for strontium uptake by a freshwater fish species [43]. In the absence of detailed information regarding strontium (and calcium) extractable fractions in the field soils (see Rigol et al [42] for methods), and mindful that the physiology and molecular biology of calcium transport in earthworms is poorly known, the present worm data must not be overinterpreted.…”
Section: Discussionsupporting
confidence: 53%
“…First, soil strontium is undoubtedly a major factor, in much the same way that the edaphic concentrations of nonessential metals (e.g., Cd and Pb) explain a large proportion of the variation in earthworm burdens [14,45]. Second, the loss of proportionality between (Sr:Ca) worm and (Sr:Ca) soil at high (Sr:Ca) soil levels conceivably reflects cation competition for, or saturation of, inwardly directed transport pathways [43]; the enhanced and preferential excretion of strontium when the cation ratio exceeds a threshold [32]; or a mutable capacity to endogenously discriminate against strontium and to favor calcium [33]. However, we found no evidence supporting a breakdown in the ability of earthworms to exclude strontium at elevated exposures [33]; rather, in the free-living populations with long strontium-exposure histories, strontium accumulation (as defined by CF and Sr:Ca ratios) in worm tissue was reduced at higher soil strontium concentrations and (Sr:Ca) soil levels.…”
Section: Discussionmentioning
confidence: 99%